Nathalie Sarraute : A Life Between - Jefferson, Ann (Book collections on Project MUSE., 2020)
"This will be the first proper biography of an important figure in late twentieth-century French literature. Nathalie Sarraute was known primarily in connection with the nouveau roman of the 1960s and 1970s, and latterly as the author of Childhood, an autobiography which was later dramatised on Broadway. She was born into a Jewish family in Russia at the beginning of the century before making her way to a new identity and a literary career in Paris. She was the author of 12 novels, six plays (still in the repertoire), and a cluster influential critical essays, and her life spanned the events and upheavals of the century: Russian revolutionaries, emigre society in Paris, women's education and their access to the professions, notably law and the French literary institution, anti-Semitism, the Occupation and her own hiding under Vichy, Sartre and Les Temps modernes, the nouveau roman, May 68, and much else. She was an unusually cosmopolitan figure, spoke excellent English, and maintained friendships with several Anglo-American figures (Maria and Eugene Jolas, Hannah Arendt, Mary McCarthy, etc.) The thread that runs through Sarraute's long life, as through her writing, is the issue of place and belonging: as the child in two step-families after her parents divorced, as a Russian emigre in France, as an assimilated Jew in French bourgeois society, as a woman in a man's world (law and literature), and as the ambivalent associate of two major literary groupings (Sartre and the nouveau roman). No biography currently exists and this will be the first. Based on archival material (including the Fonds Nathalie Sarraute in the Bibliotheque Nationale in Paris) as well as on private papers that have remained in the family, and interviews with many people who knew her, it offers a fascinating account of the lived and very varied context in which Nathalie Sarraute's work was produced and took form"--